Cell Therapy: Types, Regulation, and Clinical Benefits - El-Kadiry, Abed El-Hakim; Rafei, Moutih; Shammaa, Riam (Frontiers in Medicine, 2021)
Cell therapy practices date back to the 19th century and continue to expand on investigational and investment grounds. Cell therapy includes stem cell- and non–stem cell-based, unicellular and multicellular therapies, with different immunophenotypic profiles, isolation techniques, mechanisms of action, and regulatory levels. Following the steps of their predecessor cell therapies that have become established or commercialized, investigational and premarket approval-exempt cell therapies continue to provide patients with promising therapeutic benefits in different disease areas. In this review article, we delineate the vast types of cell therapy, including stem cell-based and non–stem cell-based cell therapies, and create the first-in-literature compilation of the different “multicellular” therapies used in clinical settings. Besides providing the nuts and bolts of FDA policies regulating their use, we discuss the benefits of cell therapies reported in 3 therapeutic areas—regenerative medicine, immune diseases, and cancer. Finally, we contemplate the recent attention shift towards combined therapy approaches, highlighting the factors that render multicellular therapies a more attractive option than their unicellular counterparts.